Association of bGH and Pit-1 gene variants with milk production traits in dairy Gyr bulls - de Mattos, Keiko Kusamura; Del Lama, Silvia Nassif; Martinez, Mario Luiz; Freitas, Ary Ferreira (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this study was to obtain genetic marker information in the Gyr breed by analyzing bGH and Pit-1 gene polymorphisms and to verify their association with milk production traits. One sample including 40 Gyr bulls were genotyped at two bGH gene restriction sites (bGH- AluI and bGH-MspI) and at one restriction site in the Pit-1 gene (Pit-1 HinfI). The bGH-MspI(-) allele was favorable for fat milk percentage. The heterozigous Pit-1 HinfI (+/-) bulls were superior for fat milk production, in relation to homozigous Pit-1 HinfI (+/+). The Pit-1 and bGH genes are strong candidates in the dairy cattle QTL search, and zebuine populations are promising samples for this purpose.